(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
A new Semi-Lagrangian scheme is proposed to discretize the surface convection-diffusion equation. The other involved equations including the level-set convection equation, the re-initialization equation and the extension equation are also solved by S-L schemes. The S-L method removes both the CFL condition and the stiffness caused by the surface Laplacian, allowing larger time step than the Eulerian method. The method is extended to the block-structured adaptive mesh. Numerical examples are given to demonstrate the efficiency of the S-L method.